Mapping the spread: insights into odontogenic maxillofacial space infections for better surgical planning: a case series analysis at a tertiary care hospital - Patel, Vraj V.; Shah, Navin S.; Shah, Parshwa N.; Mishra, Preksha S.; Jain, Rashi R.; Metaliya, Ayushi P. (International Journal of Research in Medical Sciences, 2025)
This retrospective study examines the clinical characteristics, spread patterns, management strategies, and outcomes of odontogenic maxillofacial space infections (MSI) treated at a tertiary care center between January 2021 and December 2023. A total of 20 patient records were analyzed, with a male predominance 75% and females comprising 25%. All patients were managed with incision and drainage along with intravenous antibiotics. The primary sources of infection were mandibular third molars, accounting for 40% on the right side and 35% on the left, with occasional involvement of the upper and lower, first and second molars. The submandibular space was the most frequently affected anatomical region, and multiple space involvement was common. The study highlights the mapping of the spread of infection, challenges in managing MSI, particularly in patients with systemic comorbidities such as diabetes, which contributed to increased severity and complexity. Also gives insights for managing the complications that were present in the patients. Although white blood cell (WBC) count was not a strong predictor of infection severity, its trend proved useful in monitoring treatment response. Early surgical intervention, aggressive antibiotic therapy, and vigilant clinical monitoring were associated with favorable outcomes. The findings align with existing literature regarding the predominance of male patients and the frequent implication of mandibular third molars. The study emphasizes the need for future research involving advanced diagnostic tools, evaluation of alternative antibiotic regimens, and assessment of the impact of self-medication on the microbiological profile of infections. Long-term follow-up and the integration of advanced imaging techniques could further enhance treatment strategies and contribute to improved patient outcomes.